A Case Report on Delayed Diagnosis of Turner Syndrome in a Short Statured Adolescent - Oluwayemi, I. O.; Odeyemi, A. O.; Ayeni, T. O. (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Turner syndrome has an incidence of 1/ 2500 female live births. Clinical signs such as lymphoedema in childhood, as well as short stature and delayed puberty, are common reasons for screening for Turner syndrome. Almost all affected females experience ovarian failure. We present a 15-year-old female with short stature and delayed puberty. Her mother remembered noticing swelling in both hands and feet as a child but made no sense of it. The patient's weight and height were both below the third percentile, and she exhibited no secondary sexual characteristics. The diagnosis was confirmed by the patient's karyotype (45, XO).Her serum estradiol level was low, her uterus was small, and her ovaries were atretic. Primarin was used to stimulate puberty for two years, during which she gained 3kg of weight, 4cm of height, and breast development from Tanner stage 1 to 4. Clinicians must be on the lookout for common clinical signs of Turner syndrome in order to make an early diagnosis, refer, and manage affected children for optimal growth and development.